Transparency in port governance: Setting a research agenda - Mary R. Brooks; Geraldine Knatz; Athanasios A. Pallis; Gordon Wilmsmeier (Journal of Shipping and Trade (JST), 2022)
This study examines the concept of transparency as practiced (or not) in ports. It explores the availability of information to the general public and port stakeholders through the ports' most public face-its website, studying public ports in North America, Europe, and Latin America and the Caribbean. This exploratory research centred on identifying the parameters that would be useful for the general public to have sufficient information to monitor, review and in many cases, participate in the decision-making processes carried out by the port authority, irrespective of whether or not laws mandate such disclosure. Fifty-one items were identified for the examination of each port's website, focusing primarily on four major categories: decision-making governance, port communications and accessibility, transparency in reporting and in port operational activities. Using nine items as proxies for the 51, the research reveals uneven levels of port transparency both regionally and by governance model. The study reveals a need for increasing and differentiating the existing levels and standards of transparency in the governance of the port industry, and for greater consistency between ports within and across regions. The study concludes with a research agenda for future research.
Keywords: 650